Bearing Strength of Concrete-Filled Steel Tube Reinforced with Internal Transverse Stiffened Bars under Axial Compression. (21st February 2022) - Li, Nan; Xi, Yajun; Li, He; Zhang, Guangxi; Ren, Tao; Mu, Xinhao
Abstract : A new type of square concrete-filled steel tubular (SCFST) column is proposed, which is characterized by transverse stiffened bars inside the steel tube to improve the effective constraint performance of the concrete core. The experiment of this kind of composite material under axial compression was carried out. The results showed that the bearing capacity of the SCFST column reinforced by internal transverse stiffened bars increased by 4.5%-15% than that of the ordinary SCFST column. The transverse strain is smaller than the SCFST column. As the diameter of the reinforcement increases and decreases the spacing of bars, the axial load bearing capacity increased. The transverse strain of the member decreased obviously. It is noted that the confinement performance of the concrete core of this type was improved to some extent. At the same time, based on the unified theory, the simplified calculation formula of axial compression bearing capacity is derived.